Pengaruh Persepsi Atas Kompetensi Profesional Guru dan Motivasi Belajar Terhadap Prestasi Belajar Terhadap Prestasi Belajar Matetamtika (Survei Pada SMK Swasta di Kabupaten Karawang) - Dahayati Dahayati; Sumaryoto Sumaryoto; Virgiana Virgiana (Jurnal Ilmiah Wahana Pendidikan, 2022)
From this research is to know. 1). The effect of perception on teacher's professional competence and motivation to learn together on mathematics learning achievement of SMK students in the district. Karawang. 2). Influence of Perception on Professional Competence of teachers on mathematics learning achievement of private vocational high school students in the district. Karawang. 3). The effect of learning motivation on mathematics learning achievement of private vocational high school students in Karawang Regency. The research method used is the correlational survey method. Samples taken A total of 92 students were taken at simple random. Data collection is done by testing and distributing questionnaires directly to the sample. Data analysis uses descriptive statistics such as finding the mean, median, mode, standard deviation of infrerential statistics. The results showed : 1). The effect of Perception on Teacher's Professional Competence and Learning Motivation on Mathematics Learning Achievement together has a positive impact on the learning achievement of Private Vocational High School students in Karwang Regency, this is proven by the value of sig = 0.031 < 0.05 and Fcount = 3.612. 2). Influence of Perception on the professional competence of teachers has a positive influence on increasing mathematics learning achievement in Private Vocational Schools in Karawang Regency with the results shown sig = 0.157 < 0.05 and t count = 1.427. 3). the influence of learning motivation on mathematics learning achievement has a positive influence on increasing mathematics learning achievement for private vocational high school students in Karawang Regency, this is proven by the value of Sig = 0.087 < 0.05 and t count = 1.729